Time-course transcriptome analyses of spleen in rainbow trout (Oncorhynchus mykiss) post-Flavobacterium psychrophilum infection - Deng, Furong; Wang, Di; Loch, Thomas P.; Chen, Fuguang; Lu, Tongyan; Cao, Yongsheng; Fan, Dan; Li, Shaowu (Frontiers in Immunology, 2022)
Flavobacterium psychrophilum, the etiological agent of bacterial coldwater disease and rainbow trout fry syndrome, causes considerable losses in salmonid aquaculture globally. Systemic F. psychrophilum infections in rainbow trout (Oncorhynchus mykiss) lead to a range of clinical signs, including ulcerative lesions in the skin and muscle and splenitis. Previous studies have examined the transcriptional responses of rainbow trout skeletal muscle and renal tissues to F. psychrophilum infection. However, little is known about the transcriptomic response to F. psychrophilum in spleen, which is one of the most important immune organs in rainbow trout. In the present study, we investigated the splenic transcriptome profiles in uninfected rainbow trout (CK) and F. psychrophilum infected rainbow trout at day 3 and day 7 (D3, D7) by RNA-seq analysis. Among the 7,170 differentially expressed genes (DEGs) in the three comparisons (D3vsCK, D7vsCK, D3vsD7), 1286 DEGs showed consistent up-regulation or down-regulation at D3 and D7 and were associated with pattern recognition, acute phase response, complement cascade, chemokine and cytokine signaling, and apoptosis. Our study provided the transcriptome evidence on the protective effect of acute phase response, complement systems, Th1-type responses and caspase-mediated apoptosis in the spleen of rainbow trout against F. psychrophilum. RT-qPCR analysis of eight DEGs confirmed the accuracy of the RNA-seq data. Our results reflected a general process from pathogen recognition to inflammatory cytokine generation, and delineated a putative Toll-like receptor signaling pathway in rainbow trout spleen following F. psychrophilum infection. Taken together, these results provide new insights into the molecular mechanism of the immune response to F. psychrophilum infection and are a valuable resource for future research on the immune system in rainbow trout and other salmonids.